Fuzzy Modeling In Orange Production Under Different Doses Of Sewage Sludge And Wastewater - Putti, Fernando F. [UNESP]; Lanza, Marcio H. [UNESP]; Filho, Hélio G. [UNESP]; Cremasco, Camila P. [UNESP]; Souza, Angela V. [UNESP]; Filho, Luís R. A. Gabriel [UNESP] (FapUNIFESP (SciELO), 2021)
The present work aimed to develop mathematical fuzzy models to evaluate the effects of different doses of sewage sludge and irrigation with wastewater and potable water. Such models were elaborated from an experiment carried out at the Faculty of Agronomic Sciences, in the Department of Soil and Environmental Resources, from the Sao Paulo State University, in Brazil. The experiment was carried out in a randomized block design, in a 6 × 2 factorial scheme, with 6 doses of sewage sludge (0, 25, 50, 75, 100 and 125 of the recommended dose of N), and in the presence and absence of wastewater. In the development of the fuzzy model, the Mamdani method was used for the defuzzification. As input variables, the doses of sewage sludge and the types of water were used. For the output variables, it was sought to evaluate the biometric and developmental components of the culture. It can be inferred that the model developed presented a good fit when compared to the regression model, and that the use of sewage sludge may prove to be a potential future replacement of mineral nitrogen
Keywords: biosolid; Fuzzy logic; Mamdani method.; organic matter; reuse water